A comparative study of anemia prevalence and associated factors among rural and urban adults in Bangalore, India - Shilpa Pandurangaiah; Annliya Anna Mathew; Gowthami Shettigar (International Journal Of Community Medicine And Public Health, 2026)
Background: Anemia is a major public health concern, particularly among women of reproductive age, and is influenced by socioeconomic, dietary, and health-related factors. This study aimed to compare the prevalence of anemia and associated factors among rural and urban adult populations in Bangalore. Methods: A community-based cross-sectional comparative study was conducted among 300 participants (150 urban and 150 rural residents). Sociodemographic characteristics, dietary practices, anemia awareness, iron supplementation, and hemoglobin levels were assessed using a structured questionnaire and a digital hemoglobinometer. Data were analysed using descriptive statistics and the chi-square test. Results: The overall prevalence of anemia was 29.3%, with significantly higher prevalence among urban participants (42.0%) than rural participants (16.7%) (p